PANDEMI COVID-19 SEBAGAI FAKTOR RISIKO GANGGUAN PSIKOTIK - Raisha Naomi Zahrani (Jurnal Medika Hutama, 2021)
The Corona Virus Disease 2019 (COVID-19) pandemic still cannot be controlled with the fact that morbidity and mortality rates tend to increase in many areas. Recent research has shown the presence of psychotic symptoms in the aftermath of the COVID-19 pandemic. The purpose of this study is to increase knowledge and clinician awareness in handling COVID-19 so that comprehensive management can be carried out. The method used is literature review from national and international journals. The results showed an increase in cases of schizophrenia during the COVID-19 pandemic and found evidence of COVID-19 patients with psychotic symptoms without a history of previous psychiatric disorders.